AB0726 Subclinical atherosclerosis in patients with ankylosing spondylitis. (15th June 2017) - Ismail, M; Mosallam, A; Abdelaziz, M; Moshrif, A
Abstract : Background: Systemic inflammatory response of various autoimmune diseases has been reported as a cause of accelerated atherosclerosis which is a risk factor for cardiovascular complications. Objectives: This study aimed to evaluate atherosclerosis in patients with ankylosing spondylitis (AS) and its relation to disease activity. Methods: The study was carried out on thirty AS patients, who fulfilled the modified New York criteria. Thirty apparently healthy normal volunteers, age and sex matched served as control. Complete History taking, General and systemic examination, Body mass index (BMI), Bath AS disease activity index (BASDAI), Bath AS functional index (BASFI), lipid profile, inflammatory markers and serum glucose level were done. Based on BASADI score, patients were then classified to active and inactive groups comprised 11 patients (37%) and 19 patients (63%) respectively. Carotid intima-media thickness (CIMT) was measured using real-time gray-scale sonography. The intima-media thickness (IMT) of common carotid artery, carotid bulb and internal carotid artery was determined. Results: 25 males (83.3%) and 5 females (16.7%) with mean age 39.1±12.38, their mean disease duration 13.13±8.03 while controls were 21 males (70%) and 9 females (30%) with mean age 39.7±12.6. While IMT was found significantly increased in patients (0.87±0.49) versus controls (0.5±0.12) (P<0.001), there was no significant difference regarding the presence of plaques and there was no stenosis found in cases or controls. No significant difference was found between active and inactive cases as regard to components of lipid profile. The mean IMT in active and inactive cases was 0.74±0.11 and 0.72±0.17 respectively with no significant difference. we found no significant correlation between IMT and different disease scores, ESR or CRP. Conclusions: AS patients have a higher risk for developing atherosclerosis. IMT of common carotid artery could be added as a further investigation for detection and follow up of atherosclerosis in AS patients. Disclosure of Interest: None declared